2001
DOI: 10.1063/1.1371965
|View full text |Cite
|
Sign up to set email alerts
|

Staircase-like spectral dependence of ground-state luminescence time constants in high-density InAs/GaAs quantum dots

Abstract: Time-resolved photoluminescence (PL) from InAs/GaAs quantum dots with a bimodal size distribution is used to investigate the dynamic carrier-transfer processes which couple transfer between similarly sized quantum dots and between quantum dots in different size categories. The relationship between the decay time and the emission energy appears staircaselike and the energetic positions of the steps as well as the shape can be correlated to the shape of the steady-state PL emission through a rate-equation theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…Figure 4 gives a schematic conduction-band energy diagram for the double-layer structure of sample A for the case of low and high temperatures, respectively. According to previous investigations, 5,8,11 one can suggest a time hierarchy of carrier relaxation processes. The fastest times are for intralayer and intradot carrier relaxation I , followed by interlayer carrier transfer time T , and finally the radiative ground state lifetime of seed layer dots S and second layer dots L .…”
Section: Photoluminescence Study Of Carrier Transfer Among Verticallymentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 4 gives a schematic conduction-band energy diagram for the double-layer structure of sample A for the case of low and high temperatures, respectively. According to previous investigations, 5,8,11 one can suggest a time hierarchy of carrier relaxation processes. The fastest times are for intralayer and intradot carrier relaxation I , followed by interlayer carrier transfer time T , and finally the radiative ground state lifetime of seed layer dots S and second layer dots L .…”
Section: Photoluminescence Study Of Carrier Transfer Among Verticallymentioning
confidence: 98%
“…The slight increase of peak 2 in the range of 100-150 K is a real effect. It is due to a transfer of carriers with a short lifetime in small dots of the seed layer to states with a long lifetime in large dots of the seed layer, 8 resulting in a higher equilibrium density of excited QDs. Over the same temperature range the behavior of peak 1 ͑large dots͒ is basically different.…”
Section: Photoluminescence Study Of Carrier Transfer Among Verticallymentioning
confidence: 99%
“…Moreover, though it has been demonstrated that carrier relaxation could be very fast if Auger-like recombination and impurity-assisted relaxation takes place, it is possible to observe well-resolved excited states in photoluminescence spectra [8,9]. The carrier dynamics in small InAs QDs is of great interest in relation with experimental results which have demonstrated that exciton lifetime depends on the transition energy [4,6]. The model developed by Sugawara et al [10] predicted the increase of exciton lifetime with increase of the potential confinement, what means longer exciton lifetimes for smaller QD.…”
Section: Introductionmentioning
confidence: 99%
“…Only decay at the lower-energy side of the emission band could be described with one exponential (decay time τ ), while the high-energy side shows biexponential behaviour (τ 1 and τ 2 ). The following results are obtained from [4,6]. It could be explained taking into account the separation of electrons and holes in the investigated QDs.…”
Section: Carrier Dynamics In Inas/gaas Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation